Emerging trends of microalgae bio-granulation research in wastewater treatment: A bibliometric analysis from 2011 to 2023 - Kabir ahmad, Syahirah Faraheen; Lee, Keat Teong; Vadivelu, Vel Murugan (Biocatalysis and agricultural biotechnology, 2023)
There has been an increase in the amount of focus placed on microalgae-based technology in recent years, due to its great performance in wastewater treatment, nutrient restoration, and manufacture of alternative biofuels or other high-value commodities. However, the difficulties of harvesting biomass hinder the deployment of microalgae-based technology for continuous wastewater treatment and resource recovery. This article analysed the worldwide dynamics of microalgae bio-granulation research from 2011 to 2023 based on a bibliometric analysis of 250 publications extracted from the Scopus database. The research progression, prominent contributors in the subject, and latest developments and research gaps were determined using the Scopus database. The results show a rapid increment in the annual publications, with China as the most active nation in this study field, followed by India, United State, Taiwan, Japan, South Korea and Malaysia. The research trend in microalgae bio-granulation show most research focusing on the incorporation of microalgae-bacteria symbiosis for granulation. However, there are almost no research on development of denser single-species microalgae granules without bacteria for easy harvesting via self-flocculation. Besides that, till today there are no study that investigate the effect of organic nutrient (glucose) and inorganic nutrient (sodium bicarbonate) on microalgae granulation. In addition, there are lack of studies use Chlorella Vulgaris microalgae species in bio-granulation process. An outline of possible future research was given, with a focus on technology used, nutritional media and environmental studies, and the microorganism selection. •Development of denser single-species microalgae granules without bacteria for rapid harvesting by self-flocculation.•Effect of organic and inorganic nutrients on the microalgae granules growth.•Enrichment of Chlorella vulgaris sp. microalgae via bio-granulation method for wastewater treatment.